Homecare Interest For Post Hospitalizing Patient In Pare Region - Christianto Nugroho; Suryono Suryono; Bambang Wiseno (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The main purpose of this research is for identifying the relevant market, analyzing homecare requests to the relevant patient (identify buyer, willingness to buy), determining the segment of homecare interest during covid-19. This research uses an analytic description by using a quantitative approach. The research population is posted hospitalizing patients in RSUD Pare. Data collection was gotten by disseminating questionnaires to the patient in RSUD Pare which shows the identification of respondents to the homecare during covid-19 based on demography, geography, illness, hospitalization class, patient desire. The final result of the research is found that the amount of post-hospitalizing patients with high interest is 102 respondents (59,3%), 59 respondents (34,3%) very high, and 11 respondents (6,4%) medium. Homecare can ease society to get maximal health service, which is provable by the high number of social interest to join the homecare program.